Radiation-acoustic effects at diamond-like coating deposition from the flow of hydrocarbon ions and their influence on kinetic processes - Kalinichenko, O.I.; Strel’nitskij, V.E. (Problems of Atomic Science and Technology, 2023)
Based on the model of the nonlocal thermoelastic peak (NTP) the ion generalized to the case of the ion of polyatomic molecule, the acoustic effect of low-energy ion of a hydrocarbon molecule during plasma-ion deposition of diamond-like carbon coating is investigated. The generation of a stress wave takes place as a result of the combined action of mechanisms associated with the rapid transfer of energy, momentum, and additional volume to the NTP volume. The magnitude, shape, and spatial dependence of the stress pulse generated by CH₄, C₂H₂, and C₆H₆ ions have been studied with absorption taken into account. The possibility of accelerating the diffusion of interstitial defects, as well as the possibility of brittle fracture of the coating at the interface with the substrate under the action of acoustic pulses from deposited hydrocarbon ions, is discussed. На основі моделі нелокального термопружного піка (НТП) іона, що була узагальнена на випадок іонів вуглеводневих молекул, досліджено акустичний ефект низькоенергетичного іона вуглеводневої молекули при плазмово-іонному осадженні алмазоподібного вуглецевого покриття. Генерація хвилі напруження має місце в результаті спільної дії механізмів, що пов’язані зі швидкою передачею енергії, імпульсу та додаткового об’єму в об’єм НТП. Досліджено величину, форму та просторову залежність імпульсу напруження, що генерується іонами CH₄, C₂H₂, C₆H₆ з врахуванням поглинання. Обговорюється можливість прискорення дифузії міжвузольних дефектів, а також можливість крихкого руйнування покриття на межі з підкладкою під дією акустичних імпульсів від НТП іонів вуглеводнів, що осаджуються.